Look Who’s Talking: The Snitching Paradox in a Representative Sample of Prisoners - Pyrooz, David C. (The British journal of criminology, 2021)
Snitching refers to conveying inside and potentially incriminating information about others to authorities. In contrast to prior criminological accounts of snitching, which rely on small and purposive samples, we used a probability sample of 802 male prisoners in Texas to study the status, prevalence, acceptability and correlates of snitching. We arrive at several key quantitative findings. First, snitches are positioned at the bottom of the inmate hierarchy. Second, snitching is a rare behaviour (7.6 per cent) and even rarer identity (1.8 per cent), consistent with a snitching paradox. Third, about three-fourths of respondents endorsed contingencies where snitching was permissible, primarily those involving personal ties, self-protection, or violence prevention. Finally, characteristics such as age, civic engagement, education, gang status, and arrest and imprisonment history were associated with either snitching identity, behaviour, or contingencies. Snitching is a persistent feature of social life, yet violates a sacred norm central to many criminological theories, necessitating continued inquiry into its content, enforcement and consequences.